2002
DOI: 10.1074/jbc.m207608200
|View full text |Cite
|
Sign up to set email alerts
|

PTEN Associates with the Vault Particles in HeLa Cells

Abstract: PTEN is a tumor suppressor that primarily dephosphorylates phosphatidylinositol 3,4,5-trisphosphate to down-regulate the phosphoinositide 3-kinase/Akt signaling pathway. Although the cellular functions of PTEN as a tumor suppressor have been well characterized, the mechanism by which PTEN activity is modulated by other signal molecules in vivo remains poorly understood. In searching for potential PTEN modulators through protein-protein interaction, we identified the major vault protein (MVP) as a dominant PTEN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(102 citation statements)
references
References 49 publications
2
97
0
1
Order By: Relevance
“…PTEN binds to MVP, a protein hypothesized to be a general carrier molecule for nuclear-cytoplasmic transport (Mossink et al, 2003), in yeast two-hybrid screens (Yu et al, 2002). Further analysis confirmed that this interaction occurs in both 293T and HeLa cells and localized the binding sites to the C2 domain of PTEN and the EF-hand pair (a calcium-binding motif) of MVP.…”
Section: Nuclear Ptenmentioning
confidence: 60%
“…PTEN binds to MVP, a protein hypothesized to be a general carrier molecule for nuclear-cytoplasmic transport (Mossink et al, 2003), in yeast two-hybrid screens (Yu et al, 2002). Further analysis confirmed that this interaction occurs in both 293T and HeLa cells and localized the binding sites to the C2 domain of PTEN and the EF-hand pair (a calcium-binding motif) of MVP.…”
Section: Nuclear Ptenmentioning
confidence: 60%
“…1e ; Supplementary Fig. S1d ) 17,18 . A high-density pattern of siRNA spots, such as 5,000 spots per chip, has been previously demonstrated without any obvious cross-contamination 19 .…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the interaction between PTEN and MVP depends on the presence of Ca 2+ in glutathione S-transferase pull-down assay (10). Because phosphorylation of MVP is reportedly dependent on the presence of Mg 2+ (15), and because Ca 2+ and Mg 2+ are known to exert opposing effects in many cellular functions (18,19), we hypothesized that Ca 2+ and Mg 2+ might be involved in the interaction between PTEN and MVP.…”
Section: Resultsmentioning
confidence: 99%
“…MVP reportedly interacts with the C2 domain of PTEN through the EF hand-like motif in a Ca 2+ -dependent manner in HeLa cells (10). Phosphorylation of MVP depends on the presence of Mg 2+ in PC12 cells (15), and epidermal growth factor (EGF) stimulation increases tyrosil phosphorylation of MVP in WI38 cells (12).…”
Section: Introductionmentioning
confidence: 99%